Intracellular Breakable and Ultrasound-Responsive Hybrid Microsized Containers for Selective Drug Release into Cancerous Cells; Particle and Particle Systems Characterization; Vol. 34, iss. 5 - Timin A. S. Aleksandr Sergeevich; Muslimov A. R. Albert R.; Lepik K. V. Kirill V.; Okilova M. V. Maria V.; Tcvetkov N. Y. Nikolai Y.; Shakirova A. I. Alena I.; Afanasyev B. V. Boris V.; Gorin D. A. Dmitry Aleksandrovich; Sukhorukov G. B. Gleb B. (2017, 2017)
Title screen